# How do you differentiate # f(x) = tan^2(3x) #?

Given:

This function can be written as

Hence,

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiateTo differentiate ( f(x) = \tan^2(3x) ), youTo differentiate ( f(x) = \tan^2(3x) ), use theTo differentiate ( f(x) = \tan^2(3x) ), you wouldTo differentiate ( f(x) = \tan^2(3x) ), use the chainTo differentiate ( f(x) = \tan^2(3x) ), you would use theTo differentiate ( f(x) = \tan^2(3x) ), use the chain ruleTo differentiate ( f(x) = \tan^2(3x) ), you would use the chainTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

To differentiate ( f(x) = \tan^2(3x) ), you would use the chain ruleTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ fTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule.To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivativeTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(xTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative wouldTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x)To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would beTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tanTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ fTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(xTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3xTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) =To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\secTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tanTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3xTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3xTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) \To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\secTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

ThisTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This canTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can alsoTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be writtenTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3xTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written asTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ fTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(xTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) =To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(xTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x)To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 +To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tanTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tanTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3xTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^2To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3x)\To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^2(To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3x)\sec^To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^2(3xTo differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3x)\sec^2To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^2(3x))To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3x)\sec^2(3To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^2(3x)) ]To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3x)\sec^2(3xTo differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^2(3x)) ]To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3x)\sec^2(3x)To differentiate ( f(x) = \tan^2(3x) ), use the chain rule:

[ f'(x) = 2\tan(3x)\sec^2(3x) ]

This can also be written as:

[ f'(x) = 2\tan(3x)(1 + \tan^2(3x)) ]To differentiate ( f(x) = \tan^2(3x) ), you would use the chain rule. The derivative would be:

[ f'(x) = 2\tan(3x)\sec^2(3x) \cdot 3 ]

[ f'(x) = 6\tan(3x)\sec^2(3x) ]

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7